MANAJEMEN PORTOFOLIO ASET WAKAF PRODUKTIF UNTUK PEMBANGUNAN YANG BERKELANJUTAN - RR TINI ANGGRAENI; SOFYAN RIZAL (Maqdis: Jurnal Kajian Ekonomi Islam, 2021)
To launch a sustainable economic empowerment program, a portfolio of productive waqf assets is required to determine the diversification or distribution of waqf assets in several economic sectors, including the placement of both financial assets and real assets. This research was conducted to determine the implementation of productive cash waqf empowerment programs carried out by several Nazhir institutions, so that the asset management strategy of the productive cash waqf empowerment program portfolio can be identified and the economic and social impacts of the productive cash waqf empowerment program. This research is a qualitative research conducted by observing and mapping professional Nazhir-Nazhir productive waqf programs that are scattered in the Nazhir region and have been initiated since 2015 until now. The technical analysis used is a SWOT analysis to see how much strengths, weaknesses, opportunities and threats of each Nazhir are in placing and forming a portfolio of waqf assets. The results of this research show that the basis for the placement of productive cash waqf for Nazhir institutions is the orientation of the alaihi alaih which is the target of empowerment so that sustainable development can be achieved. The formation of cash waqf asset portfolios is classified based on the types of empowerment programs. And the chosen strategy is the SO strategy, which is a strategy that uses strength and takes advantage of existing opportunities to develop cash waqf. In the SO strategy, Nazhir's collaboration with LKSPWU and Financial Technology can increase the collection of cash waqf funds collected. High literacy or socialization of waqf to the community can increase the potential for earning cash waqf. The integration or combination of cash waqf programs with waqf assets is proven to be bisaed in optimizing the utilization of waqf assets so that they can provide more benefits for the alaihi alaihi alaih. The cash waqf program that is structured also adapts to the needs of the local community, so that it is right on target and has an economic and social impact on the community. Nazhir's collaboration with educational, health, economic and social institutions facilitates the absorption of cash waqf returns. The aforementioned matters become targets and recommendations for Nazhir institutions that have launched cash waqf programs so that their placement is more optimal and right on target. Of course, also taking into account the amount of the cost of funds or cost of equity will be achieved from the results of a business feasibility study that has been done before.